APPLICATION OF IMMUNOASSAY TECHNIQUES (ELISA) FOR MONITORING ATRAZINE AND ITS METABOLITES IN THE UNSATURATED ZONE - Candela, Lucila; Cortés, Amparo; Hidalgo, Manuela; Salvadó, Victoria (Águas Subterrâneas, 2000)
The objective of the study was to develop analytical and sampling techniques for the detection of atrazine and their transformation products (DEA, DIA, DAA and HAY) in the subsurface aquatic environment at low concentrations. To validate the sampling and analytical protocol of immunoassay techniques, El Emporda area, where atrazine has been used during the last 20 years, was selected. El Emporda is located 200 Km North of Barcelona. Materials are of detritical nature (sand, silt, conglomerates) and the aquifer is multilayered. Atrazine concentrations in soil of 17 ng/g and 0.1 mg/l in water were found during a previous monitoring campaign, values suitable to be used with ELISA test. The Envirogard High Sensivity Triazine Plate Kit (Millipore ®) immunoassay kit was selected for the exercise. Water results from test application have evidenced the efficiency of the kit to semi-quantify Atrazine-DEA concentrations, and no false negative was detected. However, lack of accuracy for soil samples show the weakness of this test to detect atrazine residues. An analysis to evaluate the atrazina-DEA crossreaction showed the possibility to calculate both concentrations when both triazines are present.